Implementation of Al-Targhib Wa Al-Tarhib Method in Fiqh Learning at Syamsul Falah Islamic Boarding School - Husnul Wahan; H Usman (Sustainable, 2024)
This paper aims to determine the Implementation of the Al-Targhib Wa Al-Tarhib Method in Learning Fiqh of Worship and Its Impact on the Learning Motivation of Students at the Syamsul Falah Islamic Boarding School and to determine how important the Al-Targhib Wa Al-Tarhib Method is to be Implemented at the Syamsul Falah Islamic Boarding School. The research method used is a qualitative phenomenological research. The researcher as the main instrument collects data through observation, interviews, and document analysis. Thematic analysis is used to examine the habit of tadarus Al-Qur'an in improving students' spiritual intelligence. The results of the study indicate that the al-Targhib wa al-Tarhib Method is an important approach in Islamic education, especially at the Syamsul Falah Islamic Boarding School. This method combines motivation through rewards (al-targhib) and warnings through threats (al-tarhib), with the aim of forming students who are disciplined, responsible, and have noble character. In addition to being effective in shaping behavior, this method also imagines deep spiritual awareness. As an approach based on the Koran and the rules of fiqhiyah, al-Targhib wa al-Tarhib supports the goal of Islamic education to create a generation that is devout, moral and responsible to Allah and society. This approach combines modern educational theory with Islamic tarbiyah values ​​in a holistic manner.